Desarrollo de una aplicación móvil bajo la plataforma android, para la gestión académica de los estudiantes de la Universidad Técnica de Cotopaxi extensión La Maná periodo octubre 2014 – febrero 2015 - Vera Machuca, Carlos Alberto (2016)
The present work research is about the analysis and implementation of a mobile application in Android with the aim of the improvement in the academic management, to provide services of notifications instantaneous in Cotopaxi Technical University, La Mana Extension, through this work does emphasis to itself to the need to have a technological strategy to reach the raised aims, for the accomplishment of this search work was used the Methodology XP that helped to take a suitable process, instead of it connect according to the requirements for the development, this investigation allows to realize an interpretation to be able to control the reasons and effects, is focused basically in the technical processes of the methodology as: phase of exploration, phase of planning, phase of interaction, phase of production, phase of maintenance and phase of culmination of the project.